SM9‑based CP‑ABE Access Control Scheme under Power IoT - ZHANG Yanjie; WANG Hui; LI Yan; ZHANG Xing; ZHANG Liang; YUAN Yanfang; SHI Zhentong (Taiyuan Ligong Daxue xuebao)
[Purposes] This work has been carried out to achieve fine-grained access control based on the existing power IoT. [Methods] A ciphertext policy attribute based encryption (CPABE) scheme for power IoT scenarios based on the SM9 algorithm was proposed. [Results] On one hand, the proposed scheme solves the key escrow problem easily caused by a single authorized authority by using the multi-authority management mechanism, and achieves the traceability of malicious users and the direct revocation mechanism of agent-based attributes by establishing a two-level key generation architecture. On the other hand, the scheme makes use of the technology of outsourcing encryption and decryption computation to reduce the resource consumption of power terminal equipment in terms of computation, storage, and communication. The security and performance analyses show that the proposed scheme satisfies IND-CPA security under the DBDH assumption, and the resource overhead of the terminals in the scheme is smaller and more fixed compared with that of existing schemes.